The Role of Environmental Accounting Education and Renewable Energy Adoption in Advancing Sustainable Business Practices - Saputra, Komang Adi Kurniawan; Dewi, Ayu Aryista; Laksmi, Putu Ayu Sita; Dharmawan, Nyoman Ari Surya (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 20 No 1 (2025)DO - 10.24843/JIAB.2025.v20.i01.p02, 2025)
This study examines the impact of environmental accounting training and renewable energy utilization on green business management in the hotel industry in Bali, Indonesia, while also exploring the moderating effect of Narcissistic Personality Disorder (NPD) traits. A structured questionnaire was administered to a sample of 222 star-rated hotels, and the data were analyzed using moderated regression analysis. The results indicate that both environmental accounting training and the adoption of renewable energy significantly contribute to the effectiveness of green business management practices. However, contrary to initial expectations, NPD traits did not moderate the relationship between the independent variables and green business management. Instead, NPD appeared to weaken the positive influence of environmental accounting training on sustainable decision-making. These findings contribute to stakeholder theory by reinforcing the importance of integrating environmental accounting principles into business strategies, while also drawing attention to the psychological dimensions that may influence managerial effectiveness. The study highlights that while technical training in sustainability remains essential, individual behavioral characteristics—particularly those associated with narcissism—may hinder the successful implementation of green initiatives. Consequently, the findings underscore the need for a more holistic approach that integrates both environmental competence and psychological awareness to advance sustainable practices within the hospitality sector. Keywords : environmental accounting, renewable energy, greening business management, narcissistic personality disorder